2015
DOI: 10.1155/2015/398063
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proximal and Distal 22q11.2 Microduplications among Patients with Cleft Lip and/or Palate: A Novel Inherited Atypical 0.6 Mb Duplication

Abstract: Misalignments of low-copy repeats (LCRs) located in chromosome 22, particularly band 22q11.2, predispose to rearrangements. A variety of phenotypic features are associated with 22q11.2 microduplication syndrome which makes it challenging for the genetic counselors to recommend appropriate genetic assessment and counseling for the patients. In this study, multiplex ligation probe dependent amplification (MLPA) analysis was performed on 378 patients with cleft lip and/or palate to characterize rearrangements in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…[9][10][11] The other anomalies are quite varied and include ocular anomalies, microcephaly, cleft lip, thyroid hemiagenesis, and subtle dysmorphic facial features. 8,[12][13][14][15] In addition, an increasing number of recent studies have shown a higher incidence of autism spectrum and psychiatric disorders in those with this microduplication but, surprisingly, it has also been shown to provide some protection against schizophrenia. [16][17][18][19][20][21] There are reports of variable cognitive deficits, which are generally mild.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] The other anomalies are quite varied and include ocular anomalies, microcephaly, cleft lip, thyroid hemiagenesis, and subtle dysmorphic facial features. 8,[12][13][14][15] In addition, an increasing number of recent studies have shown a higher incidence of autism spectrum and psychiatric disorders in those with this microduplication but, surprisingly, it has also been shown to provide some protection against schizophrenia. [16][17][18][19][20][21] There are reports of variable cognitive deficits, which are generally mild.…”
Section: Discussionmentioning
confidence: 99%
“…Another child was reported postnatally by Sedghi et al 2015: the girl presented developmental delay and cleft palate. She inherited the duplication from her healthy mother.…”
Section: Duplications Between Lcr-e and F (~656 Kb)mentioning
confidence: 99%